Lei natural e bem transcendental em Tomás de Aquino - Sousa, Silva de (Sapientia, 2009)
This work treats about the connection between the notion of good and natural law in Thomas Aquinas’ Summa Theologica: S.th. Ia, q. 5, a. 1 e S.th. Ia-IIae, q. 94, a. 2. The session about natural law will be discussed under the transcendental notion of good. This notion will be situated at the analysis context of Jan Aertsen about the Doctrine of the Transcendentals. In a certain way, reconstructing Aertsen perspective, we will argue that a wider transcendental basis of morality, according to St. Thomas, can’t lack the reference to God’s eternal law.